FACIAL SOFT TISSUE ANALYSIS AMONG VARIOUS VERTICAL FACIAL PATTERNS - Jeelani, Waqar; Fida, Mubassar; Shaikh, Attiya (Journal of Ayub Medical College Abbottabad, 2016)
Background: The emergence of soft tissue paradigm in orthodontics has made various soft tissue parameters an integral part of the orthodontic problem list. The purpose of this study was to determine and compare various facial soft tissue parameters on lateral cephalograms among patients with short, average and long facial patterns. Methods: A cross-sectional study was conducted on the lateral cephalograms of 180 adult subjects divided into three equal groups, i.e., short, average and long face according to the vertical facial pattern. Incisal display at rest, nose height, upper and lower lip lengths, degree of lip procumbency and the nasolabial angle were measured for each individual. The gender differences for these soft tissue parameters were determined using Mann-Whitney U test while the comparison among different facial patterns was performed using Kruskal-Wallis test. Results: Significant differences in the incisal display at rest, total nasal height, lip procumbency, the nasolabial angle and the upper and lower lip lengths were found among the three vertical facial patterns. A significant positive correlation of nose and lip dimensions was found with the underlying skeletal pattern. Similarly, the incisal display at rest, upper and lower lip procumbency and the nasolabial angle were significantly correlated with the lower anterior facial height. Conclusion: Short facial pattern is associated with minimal incisal display, recumbent upper and lower lips and acute nasolabial angle while the long facial pattern is associated with excessive incisal display, procumbent upper and lower lips and obtuse nasolabial angle.